A Novel Approach for Intrusion Detection System Using Equalized Multi-Routing Protocol in MANET - Jayakanth, J. J.; Madhumati, G. L.; Dhanesh, Lavanya; Saranya, Palanivelu; Vijayprasath, S.; Sambooranalaxmi, S. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
In recent years, a Mobile Ad Hoc Network (MANET) has emerged as a Wireless Communication Network (WCN) consisting of several highly mobile nodes moving in various commands. It uses an Intrusion Detection System (IDS), a monitoring parameter, to detect network-related activity by alerting the service operations centre. Since MANET has no infrastructure, nodes can connect randomly. Ad hoc networks, however, are more vulnerable than wired environments; this vulnerability also affects the MANET characteristics. However, protecting MANETs against malicious nodes randomly integrated into the network is a significant challenge. To solve this problem, the first stage of malicious nodes can be rejected using a Trust Table (TT) to bring healthy communication to the network. Furthermore, we verify the performance of IDS based on direct Trust, indirect Trust, and error, using the Trust Routing Factor (TRF) method. Second, we use an Initialized Energy Node (IEN) method to find out whether the remaining energy range of the communication nodes in the network is at the minimum or maximum energy ratio and energy consumption. Next, we use Cluster Head (CH) can be selected Using Fuzzy Clustering Naive Bayes (fuzzy CNB) strategies to solve the problems of MANET's energy degradation and transmission delay. Finally, we proposed an optimal selection based on a new Equalised Multi-Routing Protocol (EMRP) method to generate multiple paths from the source to the destination node using maximum Fitness Measure (FM). The simulation result in the EMRP method can obtain maximum energy, efficiency, detection rate, and minimum delay in the presence of an attack.